Enhanced future variability during India's rainy season. Issue 12 (21st June 2013) - Menon, Arathy; Levermann, Anders; Schewe, Jacob
<x xml:space="preserve">Abstract</x> [1] The Indian summer monsoon shapes the livelihood of a large share of the world's population. About 80% of annual precipitation over India occurs during the monsoon season from June through September. Next to its seasonal mean rainfall, the day‐to‐day variability is crucial for the risk of flooding, national water supply, and agricultural productivity. Here we show that the latest ensemble of climate model simulations, prepared for the AR‐5 of the Intergovernmental Panel on Climate Change, consistently projects significant increases in day‐to‐day rainfall variability under unmitigated climate change. The relative increase by the period 2071–2100 with respect to the control period 1871–1900 ranges from 13% to 50% under the strongest scenario (Representative Concentration Pathways, RCP‐8.5), in the 10 models with the most realistic monsoon climatology; and 13% to 85% when all the 20 models are considered. The spread across models reduces when variability increase per degree of global warming is considered, which is independent of the scenario in most models, and is 8% ± 4%/K on average. This consistent projection across 20 comprehensive climate models provides confidence in the results and suggests the necessity of profound adaptation measures in the case of unmitigated climate change.